Synthesis and tensioactive properties of PEO-b-polyphosphate copolymers1. Issue 35 (18th April 2015) - Vanslambrouck, S.; Clément, B.; Riva, R.; Koole, L. H.; Molin, D. G. M.; Broze, G.; Lecomte, P.; Jérôme, C.
<x xml:space="preserve">Abstract</x> Investigation of the micellization of degradable polyphosphoester based surfactants following a solvent-free process: the role of the pendent chain.